Optimizing use of empirical antibiotics in late preterm neonates at risk of early-onset sepsis - James, Jemila; Kailas, Lalitha; Nair, P M C; Shaji, M (Indian Journal of Child Health, 2019)
Background: In sick neonates, we are posed to treat suspected or proven infection. However, the vast majority of newborn babies who are given antibiotics do not have any infection. Objective: The objective of this study was to optimize the use of empirical antibiotic therapy in late preterms who are asymptomatic with maternal risk and symptomatic neonates without maternal risk for early-onset sepsis (EOS) and to estimate the rate of risk increase in onset of symptoms in neonates exposed to maternal risk factor for EOS. Methods: In this descriptive study, late preterm neonates (34+0–36+6 weeks) who are asymptomatic at birth with and without maternal risk factor for EOS at birth were subjected to clinical assessment of sensorium, temperature, oxygenation status, perfusion, and skin color, starting after 1 h of initial stabilization till discharge from hospital. Sepsis screen (C-reactive protein and absolute neutrophil count) was obtained at 24 h and 48 h of age from these asymptomatic late preterms. Results: A total of 135 late preterm neonates (34+0–36+6 weeks) recruited during the study period were included for analysis. The presence of maternal risk factor for EOS has shown no statistical significance in relation to the presence of symptoms at birth odds ratio 0.66, 95% confident interval (0.24–1.8) p=0.42. Conclusion: In our study, as maternal risk factor for sepsis has shown no statistical significance in relation to the presence of symptoms at birth, antibiotic use can be restricted to only those babies who have clinical worsening over 24–48 h of observation and/or along with supportive evidence of positive sepsis screen and/or blood culture, irrespective of the presence or absence of maternal risk for EOS.